The PmlI-PmlR Quorum-Sensing System in Burkholderia pseudomallei Plays a Key Role in Virulence and Modulates Production of the MprA Protease - Valade, E. (American Society for Microbiology, 2004)
Burkholderia pseudomallei is the causative agent of melioidosis, an often fatal infection of humans and animals. The virulence of this pathogen is thought to depend on a number of secreted proteins, including the MprA metalloprotease. We observed that MprA is produced upon entry into the stationary phase, when the cell density is high, and this prompted us to study cell density-dependent regulation in B. pseudomallei. A search of the B. pseudomallei genome led to identification of a quorum-sensing system involving the LuxI-LuxR homologs PmlI-PmlR. PmlI directed the synthesis of an N-acylhomoserine lactone identified as N-decanoylhomoserine lactone. A B. pseudomallei pmlI mutant was significantly less virulent than the parental strain in a murine model of infection by the intraperitoneal, subcutaneous, and intranasal routes. Inactivation of pmlI resulted in overproduction of MprA at the onset of the stationary phase. A wild-type phenotype was restored following complementation with pmlI or addition of cell-free culture supernatant. In contrast, there was no significant difference between the virulence of a B. pseudomallei mprA mutant and the virulence of the wild-type strain. These results suggest that the PmlI-PmlR quorum-sensing system of B. pseudomallei is essential for full virulence in a mouse model and downregulates the production of MprA at a high cell density.